Reactivity of immune system cells to adrenaline and acetylcholine in patients with primary and recurrent posterior uveitis - Коновалова, Наталія Валеріївна; Храменко, Наталія Іванівна; Величко, Людмила Миколаївна; Богданова, Олександра Вікторівна (My University, 2024)
Posterior uveitis is a poly etiological group of diseases, which is distinguished by polymorphism of clinical manifestations, long-term chronic and recurrent nature of the process, frequent damage to both eyes, the development of various early and late complications, loss of ability to work for a signifcant period and disability of young people Aim: to determine the level of expression of adrenaline and acetylcholine reception on peripheral blood lymphocytes in patients with primary and recurrent posterior uveitis during diferent periods of the disease Methods: The assessment of the specifc reactivity of lymphocytes to the neurotransmitters adrenaline and acetylcholine was carried out using a complex method for assessing the individual sensitivity of the body to drugs (bio regulators) Results: The absolute and relative levels of adreno/acetylcholine reception in patients with posterior uveitis were increased compared to the norm by 1.8–2.8 times/1.6–2.4 times, respectively. When the process recurs during the period of active infammation, higher absolute levels of expression of drenaline/acetylcholine receptors are signifcantly determined by 12.6% and 31.7%,respectively, in comparison with the period of remission. However, even during the period of remission, expression levels of adrenaline/acetylcholine receptors in patients with posterior uveitis remain above normal. We have determined that the chance that with posterior uveitis there will be an increased level of expression of adrenoreception/acetylcholine reception on peripheral blood lymphocytes with posterior uveitis is 67.5 times/23.6 times higher than normal. A strong direct connection has also been established between the expression of adrenoreception/acetylcholine reception on lymphocytes and the number of T-cells and T-helpers, a direct connection of lesser strength with B-cells, which refects largely the connection with cellular immunity, and to a lesser extent with humoral immunity. As well as cell subpopulations with such biomarkers as markers of early activation of lymphocytes (CD-5),autoimmune aggression (CD-25), adhesion molecules as a marker of infammation (CD-54),“apoptosis” marker CD-95 (Fas/APO-1) have a direct correlation with the level of expression adrenaline/acetylcholine Conclusions: The level of expression of adrenaline/acetylcholine on peripheral blood lymphocytes may serve as one of the nonspecifc biomarkers of activation of the infammatory process in posterior uveitis.